Variability in the Gas Composition of the Popocatépetl Volcanic Plume - Taquet, Noémie; Stremme, Wolfgang; Grutter, Michel; Baylón, Jorge; Bezanilla, Alejandro; Schiavo, Benedetto; Rivera, Claudia; Campion, Robin; Boulesteix, Thomas; Nieto-Torres, Amiel; Espinasa-Pereña, Ramón; Blumenstock, Thomas; et al. (Frontiers in Earth Science, 2019)
Long term time series of volcanic plumes composition constitute valuable indicators of the evolution of the magmatic and volcanic systems. We present here a 4 years long time series of molecular ratios of HF/HCl, HCl/SO2 , SiF4 /SO2 , HF/SiF4 measured in the Popocat epetl 's volcanic plume using ground-based solar absorption FTIR spectroscopy. The instrument based in the NDACC (Network for the Detection of Atmospheric Composition Change) station of Altzomoni site, facing the Popocatepetl volcano, provides an unrivalled precision. The computed mean and standard deviation of the HF/HCl and HCl/SO2 ratios for this period were found to be 0.24±0.03 and 0.11±0.03, respectively. SiF4 was detected in three occasions and the SiF4 /SO2 ratios ranged between (1.9±0.5) x 10e−3 and (9.9±0.4) x 10e−3. The HBr/HCl and HBr/SO2 ratios remained below their detection limit (1.25 x 10e−4 and 1.25 x 10e−5, respectively), given that a part of the HBr has already been converted to other bromine species (e.g.: BrO, Br2 ) a few kilometers downwind of the crater. Combining our time-series with satellite SO2 fluxes and seismic data, we explain the significant long-term HCl/SO2 variations by changes in the conduit and edifice permeabilities, impacting the deep and shallow degassing processes. The high temporal resolution of the data also allows capturing the variation of the volcanic plume composition preceding and induced by a common moderate explosion at Popocatepetl volcano. We interpret the observed variations of the HCl/SO2 ratio during the explosion as a progressive decompression and release of the gas (Taquet et al. 2017) stored in the deep conduit. SiF4 /HCl versus HF/HCl is found to have a linear relation with a slope of -1/4 during the explosions, which implies a conservation of fluorine.